The Development of Pedagogical Content Knowledge about Teaching Redox Reactions in German Chemistry Teacher Education - Luciane F. Goes; Carmen Fernandez; Ingo Eilks (MDPI AG, 2020)
This paper presents a qualitative cross-level study with a focus on prospective and in-service teachers' pedagogical content knowledge (PCK) of redox reactions in Germany. The objective was to investigate and analyze the differences in PCK between those in pre-service teacher education and those working as teachers. The sample included four different groups: bachelor's students, master's students, graduate teacher trainees, and in-service teachers. Data were collected by an online questionnaire and semi-structured interviews. The online questionnaire was developed based on misconceptions and learning difficulties regarding redox reactions. Sixty-two participants answered the questionnaire and the interviews were carried out with twelve participants. The results revealed that teaching experience makes a difference. Pre-service teachers described quite traditional and content-focused approaches while experienced teachers emphasized the application of the content. Experienced teachers showed a more developed repertoire of instructional strategies. Participants differed also in their knowledge about learners and the curriculum. Concerning assessment, practices were at a quite general pedagogical knowledge level and not domain-specific. Although teacher education in Germany includes several chances for internships, it is suggested that central aspects of teachers' PCK start to develop and settle only when they begin to work as teachers. To avoid perpetuating traditional practices, investment in continuous professional development is needed.